Pinos anatômicos cimentados com agentes resinosos em diferentes comprimentos radiculares :estudo da interface e da resistência de união - Souza, Niélli Caetano de (2015)
The objectives of the study were to evaluate the influence of the depth of cement, the cement type and mechanical cycling through the pullout bond strength of direct anatomical post in fragile bovine roots and assess the thickness of resin cements in different root thirds of direct anatomical post and fiber post in human single-rooted. Eighty bovine roots were obtained for the bond strength by pullout. The canals were endodontically treated and extended with diamond burs. The roots were divided in two groups: G1 - direct anatomical posts cemented with RelyX ARC; G2 - direct anatomical posts cemented with RelyX U200. Both groups were divided in two subgroups, each subgroup (n = 10) cemented with a depth of 5 mm or 10 mm. Half of the specimens of each depth was submitted to mechanical cycling. The specimens were submitted to pullout test in a universal testing machine. The results were analyzed by ANOVA three factors (α=0.05). To study the thickness of the resin cement, 40 single-rooted human upper anterior teeth were obtained. The teeth were endodontically treated and weakened with drill Largo and diamond burs in a depth of 10 mm.The teeth were randomly divided in four groups (n = 10): Group 1 - fiber post + RelyX ARC; Group 2 - fiber post + RelyX U200 +; Group 3 - anatomical post + RelyX ARC; Group 4 - anatomical post + RelyX U200. The dyes 0.1% Fluorescein and 0.1% Rhodamine B isothiocyanate were added to adhesive system and resin cement, respectively. After cementation, the roots were sectioned in slices and observed by confocal laser scanning microscopy. Datas were analyzed by ANOVA followed by Tukey test (α=0.05). For the pullout test, the resin cement factor (p = 0.0001) and mechanical loading factor (p = 0.0001) were significant. The bond strength of RelyX U200 (6.47 MPa) was statistically superior to RelyX ARC (5.51 MPa). The depth of cementation factor was not significant (p=0.328). However, the interaction between depth and mechanical cycling was significant (p=0.0001). For a depth of 5 mm of cementation, the average bond strength of samples without mechanical cycling (6.98 MPa) was statistically higher to samples with mechanical cycling (4.78 MPa). For the depth of cementation of 10 mm, there was no statistical difference between the samples with and without mechanical cycling.For analysis of the resin cement thickness, post, cement and root thirds influenced the thickness of the resin cement (p <0.001). The thickness of resin cement was significantly lower in anatomical post groups than in fiber post groups, except in the apical third of the canal. There was no significant statistical difference between the cements for the direct anatomical post; for the fiber posts, only the cervical third showed a statistically significant difference between the cements. It was concluded that the direct anatomical posts cemented in the 10 mm depth obtained the best results with RelyX U200, regardless of mechanical cycling. In addition, in weakened roots, the preparation of direct anatomical post allows the better adaptation of post to the channel walls, favoring the formation of a thin and uniform cement film.